PENDIDIKAN ISLAM, GLOBALISASI TEKNOLOGI INFORMASI, DAN MORALITAS BANGSA (Eksistensi Pendidikan Islam di Era Globalisasi Teknologi Informasi) - Zaenal Mustakim (Jurnal Forum Tarbiyah, 2013)
The constant development of information technology (Science and Technology) is something that can not be avoided. The logicalÂ  consequence of the development of these technologies is the ease of access to all information that makes the young generation fall asleep with the negative impact. National morality is one of the problems caused by the development technology that increase out of control. Therefore, to anticipate such problems, it needs well systematic efforts and full wisdom. Such efforts can be initiated from Islamic education. In implementing education, it should be designed as maximum as possible so that offers applicable steps.